2023
DOI: 10.3389/fgene.2022.1048476
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of two contrasting pigeon pea (Cajanus cajan) genotypes in response to waterlogging stress

Abstract: 2023), Transcriptome profiling of two contrasting pigeon pea (Cajanus cajan) genotypes in response to waterlogging stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Waterlogging stress is a major production constraint for grain legumes such as mungbean ( Amin et al, 2017 ), black gram ( Kyu et al, 2021 ), pigeonpea ( Tyagi et al, 2023 ), soybean ( Sathi et al, 2022 ), which are highly vulnerable to waterlogging stress, particularly during early crop growth stages. Further, climate change models projected that crop productivity would decline more frequently due to waterlogging and other abiotic constraints ( Caretta et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Waterlogging stress is a major production constraint for grain legumes such as mungbean ( Amin et al, 2017 ), black gram ( Kyu et al, 2021 ), pigeonpea ( Tyagi et al, 2023 ), soybean ( Sathi et al, 2022 ), which are highly vulnerable to waterlogging stress, particularly during early crop growth stages. Further, climate change models projected that crop productivity would decline more frequently due to waterlogging and other abiotic constraints ( Caretta et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, integrating multiomics approaches to decipher the molecular mechanisms of host–Cr interactions and their signaling and thus identify potential target genes can be further utilized for the development of Cr-resistant cultivars via genetic engineering. In the last decade, the advent of high-throughput ‘omics’ technologies has generated extensive information on the regulatory mechanisms of plant resistance to various biotic and abiotic stresses [ 156 , 157 , 158 ]. Similarly, omics studies and the integration of bioinformatics resources have helped in understanding the molecular mechanisms regulating heavy metal accumulation in plants and the responses of plants to these stresses.…”
Section: Mitigation Of Chromium Toxicity In Sustainable Agriculturementioning
confidence: 99%
“…According to a recent study by Cao et al [ 137 ], the majority of the transcription factors (TFs) that are differentially expressed in cassava under waterlogging stress are encoded by genes from the NAC , MYB , AP2/ERF , and WRKY families, indicating that these genes are important in waterlogging resilience. Recently, a transcriptome study in pigeon pea plants under waterlogging stress was carried out which revealed a diverse number of differentially expressed genes associated with their physiological, anatomical adaptive traits [ 138 ]. Similarly, transcriptome analysis in Vigna vexillata roots after waterlogging stress showed many important differentially expressed genes linked with ET biosynthesis, glycolysis, and fermentation [ 139 ].…”
Section: Strategies For Improving Waterlogging Tolerance In Plants: P...mentioning
confidence: 99%